El juego cooperativo para el desarrollo socioemocional en niños de 4 a 5 años de la Unidad Educativa "Verbo Divino", provincia Bolívar, cantón Guaranda, periodo 2025. - Solano Granado, Damaris Dayana (2025)
This research examines the implementation of cooperative games as a strategy for the socio-emotional development of 4- and 5-year-old children at the Verbo Divino Educational Unit in the city of Guaranda. This research examines the attitudes children display both in the classroom and at the institution. The main objective is to determine cooperative play strategies that promote socio-emotional development in 4- and 5-year- old students. Qualitative research was used as a methodology for this purpose, as it provides greater insight into the current situation. Its design is explanatory, and its purpose reflects applied quality. Its type is descriptive and bibliographic, and its research location is field-based. For this purpose, a survey was administered to the school's teachers and an observation form was administered to the children. The results showed that the alternative with the highest percentage of progress was considered to be in progress, followed by those at the beginning and finally those who have reached completion. Therefore, cooperative games are recommended as the best way to support the social and emotional development of 4- and 5-year-old children.